Uji Potensi Epigallocatechin Gallate Kulit Pisang Raja (Musa paradisiaca var. Raja) terhadap Caspase 3 melalui Granzyme B Pathway pada Mencit (Mus musculus) Model Sepsis Berbasis in Silico - Lisa Savitri; Elfred Rinaldo Kasimo; Lian Pandu Farendra; Iza Dwi Muslikha (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Yellow ripe banana skin is rich in flavonoid compounds, and contains other phenolic compounds. The presence of flavonoids and other phenolic compounds in banana peels needs to be identified and tested for their activities, so as to increase the utilization of banana waste more optimally. Besides bananas also contain high epigallocatechin gallate (EGCG). EGCG is well known for its wide spectrum of biological activity as an anti-oxidative, anti-inflammatory and anti-tumor agent. The purpose of this study was to determine the potential of EGCG of plantain (Musa paradisiaca var. Raja) peel against caspase 3 through granzyme B pathway in mice (Mus musculus) sepsis model based on silico. Analysis of the potential of EGCG on mice was carried out using the application http://stitch.embl.de/. STITCH is a database of known and predicted interactions between chemicals and proteins. Interactions include direct (physical) and indirect (functional) associations, STITCH data derived from computational predictions, from the transfer of knowledge between organisms, and from interactions collected from other (primary) databases. Analysis of the mechanism of epigallocatechin gallate of plantain peel against capase 3 in sepsis mice using bioinformatics application https://www.kegg.jp/. Based on the results of the analysis it can be seen that EGCG can be used as a promising target agent candidate for plasma membrane proteins, such as epidermal growth factor receptors. In addition, action mechanisms have been demonstrated that rely on inhibition of ERK1 / 2, p38 MAPK, NF-κB, and vascular endothelial growth factors. Furthermore, EGCG and its derivatives are used in proteasome inhibition and they are involved in epigenetic mechanisms.